2015
DOI: 10.1063/1.4923318
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behaviors of a Zr-based bulk metallic glass under ramp wave and shock wave loading

Abstract: Dynamic behaviors of Zr51Ti5Ni10Cu25Al9 bulk metallic glass were investigated using electric gun and magnetically driven isentropic compression device which provide shock and ramp wave loading respectively. Double-wave structure was observed under shock compression while three-wave structure was observed under ramp compression in 0 ∼ 18GPa. The HEL of Zr51Ti5Ni10Cu25Al9 is 8.97 ± 0.61GPa and IEL is 8.8 ± 0.3GPa, respectively. Strength of Zr51Ti5Ni10Cu25Al9 estimated from HEL is 5.0 ± 0.3GPa while the strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In [5] a Zr-based BMG subjected to uniaxial tensile strain in plate-impact experiments under compressive loading with peak stresses ranging between 3.9 and 6.1 GPa, in the result of wave interactions produced tensile loading leading to spallation in the BMG samples. Tensile fracture or spall, observed in these experiments, was initiated at a tensile stress of 3.8±0.3 GPa and 3.6±0.1 GPa in [7]; this value was independent of the impact stress and is significantly higher than that observed for crystalline metals. T. Mashimo with coauthors [8] bulk metallic glass (BMG) were investigated by using a planar impact technique on an electrical explosion of conductor (EEC) installation.…”
Section: Dynamic Behavior Of Bulk Metallic Glass On the Base Of Timentioning
confidence: 55%
See 2 more Smart Citations
“…In [5] a Zr-based BMG subjected to uniaxial tensile strain in plate-impact experiments under compressive loading with peak stresses ranging between 3.9 and 6.1 GPa, in the result of wave interactions produced tensile loading leading to spallation in the BMG samples. Tensile fracture or spall, observed in these experiments, was initiated at a tensile stress of 3.8±0.3 GPa and 3.6±0.1 GPa in [7]; this value was independent of the impact stress and is significantly higher than that observed for crystalline metals. T. Mashimo with coauthors [8] bulk metallic glass (BMG) were investigated by using a planar impact technique on an electrical explosion of conductor (EEC) installation.…”
Section: Dynamic Behavior Of Bulk Metallic Glass On the Base Of Timentioning
confidence: 55%
“…Several Us-Up curves of Zr based BMGs reported in literatures [7]. It can be seen that a kink appears at particle velocity 380m/s ~ 660m/s (pressure range 14GPa ~ 26GPa) for Zr-based BMGs, and for Zr 57 Nb 5 Cu 15.4 Ni 12.6 Al 10 BMG, a second kink appears at 1.7km/s.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The shock wave instability related to pressure just above the HEL highlighted a strain-softening response that is well known in static to be a characteristic response upon loadings exceeding the elastic domain. Smirnov et al and Luo et al also reported the HEL of a Zr 55 AlNiCu [14] and a Zr 51 Ti 5 Ni 10 Cu 25 Al 9 [15] BMG, respectively, to be around 4.5 GPa and 8.9 GPa. Arman et al used molecular dynamic simulations to follow the evolution of icosahedral structures on a binary Cu 46 Zr 54 BMG for pressure range around the elasto-plastic transition to determine how some icosahedral configurations contribute to strain-softening [13].…”
Section: Introductionmentioning
confidence: 93%